(untitled) (Studia Prawnicze / The Legal Studies, 2022)
W artykule podjęto problem sądowego stosowania konstytucji we współczesnych realiach kryzysu polskiego porządku konstytucyjnego, rysującego się od jesieni 2015 r. Punktem wyjścia w części 1 jest przypomnienie zasady konstytucjonalizmu, wymagającej traktowania konstytucji jako instrumentu prawnego, więc nadającego się do stosowania w procedurach sądowych. Wyróżnia się trzy podstawowe formy tego stosowania: stosowanie samoistne norm konstytucyjnych, współstosowanie norm konstytucyjnych i ustawowych, a także stosowanie kolizyjne (zwłaszcza kontrolę konstytucyjności ustaw). Dalsze rozważania koncentrują się na stosowaniu kolizyjnym. W części 2 analizowany jest kontekst wprowadzenia sądowej kontroli w Polsce w końcu minionego stulecia. Wzorem Europy kontynentalnej zdecydowano się na wprowadzenie odrębnego sądu konstytucyjnego (model kelsenowski). Przemawiały za tym argumenty tradycyjne dotyczące roli ustawy, sądów „sądowych” oraz sądu konstytucyjnego. Konstytucja RP z 1997 r. skłaniała się ku monopolowi TK w kontroli konstytucyjności ustaw, ale sądy nie w pełni ten monopol uznawały. Dzisiejsza perspektywa, poruszona w części 3, jest jednak inna, bo z jednej strony kryzys konstytucyjny doprowadził do politycznej absorpcji TK, a z drugiej – sądy „sądowe” nauczyły się stosowania konstytucji i są dziś zdolne do incydentalnej kontroli konstytucyjności ustaw. Prowadzi to do konkluzji, że de lege lata, istnieją argumenty wspierające samodzielność sądów w sprawowaniu tej kontroli, a de lege ferenda, konieczne będzie rozważenie, czy istnienie odrębnego sądu konstytucyjnego zasługuje w Polsce na kontynuację. The article deals with the problem of the judicial application of the Constitution in the ongoing constitutional crisis in Poland. The starting point (part I) is to recall the principle of constitutionalism. This entails treating the Constitution as a legal instrument, which could (and should) serve as a norm of reference in specific cases or controversies decided by the courts. There are three basic forms of the judicial application: the autonomous application of constitutional norms, the co-application of constitutional and statutory norms and and – discused in this article - the judicial review of constitutionality of statutory norms. Part II of the article contains an analysis of the context in which constitutional review in Poland was introduced at the end of the last century. Following the example of continental Europe, it was decided to establish a separate constitutional court (the Kelsenian model). This was supported by traditional arguments concerning the role of statutes, the capacities of regular courts and the advantages of a ‘new’ constitutional court. The 1997 Constitution tended towards a monopoly of the Constitutional Tribunal in the review of the constitutionality of statutes. However, the regular courts (including the Supreme Court and the High Administrative Court) have never recognised this monopoly unconditionally. Today’s perspective (part III) is different. On the one hand, the constitutional crisis has led to the political absorption of the Constitutional Tribunal. It raises the more general question of what the necessary traits of a ‘constitutional court’ are. On the other hand, the regular courts have learnt to apply the Constitution (as well as other supra-statutory instruments, such as EU law and ECHR law) and are now capable of exercising an incidental review of statutes. This leads to the conclusion that, de lege lata, there are arguments supporting the autonomy of courts in exercising incidental review and that, de lege ferenda, it might be necessary to consider whether a separate constitutional court in Poland should continue to exist.